ANALISIS KOMPARATIF DASAR FILOSOFIS PENDIDIKAN ISLAM DAN FILSAFAT BARAT: STUDI PUSTAKA TENTANG TUJUAN DAN HAKIKAT PENDIDIKAN - Popy Indar Sari; Nurkholis Ramdhani; Risan Rusli; Romli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to comparatively analyze the philosophical foundations of Islamic education and Western philosophy, particularly in terms of the objectives and the nature of education. This research employs a library research method with a qualitative descriptive-analytical approach. The data sources are derived from various academic literatures such as books, journals, and scholarly works relevant to the study. Data collection is conducted through documentation techniques, while data analysis uses content analysis and comparative methods. The results indicate that Islamic education is grounded in revelation (the Qur’an and Hadith) and reason, with a theocentric orientation emphasizing the balance of spiritual, intellectual, and moral aspects. In contrast, Western educational philosophy is based on rationalism, empiricism, and humanism, with an anthropocentric orientation focusing on the optimal development of individual potential. In terms of objectives, Islamic education aims at achieving both worldly and hereafter happiness, whereas Western education emphasizes progress, freedom, and worldly well-being. Regarding its nature, Islamic education is viewed as a form of worship and moral development, while Western education is seen as a process of humanization. Despite these fundamental differences, both share similarities in developing human potential. Therefore, an integration of spiritual and rational values is necessary to create a comprehensive educational system that is relevant to contemporary challenges